Using the NONCODE Database Resource. Issue 1 (27th June 2017) - Xiyuan, Li; Dechao, Bu; Liang, Sun; Yang, Wu; Shuangsang, Fang; Hui, Li; Haitao, Luo; Chunlong, Luo; Wenzheng, Fang; Runsheng, Chen; Yi, Zhao
Abstract: NONCODE is a comprehensive database that aims to present the most complete collection and annotation of non‐coding RNAs, especially long non‐coding RNAs (lncRNA genes), and thus NONCODE is essential to modern biological and medical research. Scientists are producing a flood of new data from which new lncRNA genes and lncRNA‐disease relationships are continually being identified. NONCODE assimilates such information from a wide variety of sources including published articles, RNA‐seq data, micro‐array data and databases on genetic variation (dbSNP) and genome‐wide associations (GWAS). NONCODE organizes all this information and makes it freely available to the public via the Internet. The NONCODE protocol provides step‐by‐step instructions on how to browse and search lncRNA information such as sequence, expression, and disease relationships, how to use the tools for functional prediction, species conservation assays, blast analysis, identifier conversion, and, finally, how to submit sequences to identify lncRNA genes. As of Dec 2016, NONCODE has cataloged 487, 851 lncRNA genes sequenced from 16 species. © 2017 by John Wiley & Sons, Inc.